1995
DOI: 10.1111/j.1744-7348.1995.tb05389.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on leaf appearance and canopy establishment in fibre hemp (Cannabis sativa L.)

Abstract: SUMMARY The effects of temperature on the development and growth of hemp (Cannabis sativa L.) have never been quantified. Therefore, to establish the effect of temperature on leaf appearance and canopy establishment of fibre hemp under controlled and field conditions, plants were grown in growth chambers at 11 regimes with average temperatures between 10°C and 28°C, and three cultivars were sown in the field in March, April and May in 1990, 1991 and 1992. In the field, thermal time (base 0°C) between sowing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In addition, temperature is an important factor for canopy formation in fiber hemp. A study showed that the rate of leaf appearance and stem elongation linearly increased as temperature rises from 10 o C to 28 o C (Van Der Werf et al 1995 ). Due to global warming, agricultural crops including Cannabis plants encounter multiplexed environmental stresses of which extreme heat and drought are the most impactful.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperature is an important factor for canopy formation in fiber hemp. A study showed that the rate of leaf appearance and stem elongation linearly increased as temperature rises from 10 o C to 28 o C (Van Der Werf et al 1995 ). Due to global warming, agricultural crops including Cannabis plants encounter multiplexed environmental stresses of which extreme heat and drought are the most impactful.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the temperatures rise above 35 o C, the soil coverage works negatively. Werf et al (1995) observed that rates of leaf appearance and stem elongation increased linearly with temperature between 10°C and 28°C. Kobza et al (1987) noticed that leaf temperature on wheat was 15-25 o C.…”
Section: Light (%) At the Base Of The Cropmentioning
confidence: 96%
“…The first publication with a detailed response of greenhouse cultivated cannabis to nitrogen (N), phosphorus (P), and potassium (K) was published in 1977 (Coffman and Gentner, 1977). Furthermore, two parallel reports by HMG et al, in 1995 discussed the impact of nitrogen fertilization on sex expression in hemp (van der Werf and van den Berg, 1995), and the effect of temperature on leaf and canopy formation (van der Werf et al, 1995). Importantly, most physiological studies in the second and third period (Figure 1A) were published for hemp with a focus on photosynthetic response and biomass yield with varying conditions such as temperature, water availability, nitrogen, and mineral nutrition (Amaducci et al, 2002;Aubin et al, 2015;Finnan and Burke, 2013;Papastylianou et al, 2018;Tang et al, 2017Tang et al, , 2018.…”
Section: Cannabis Sativa L Physiology and Legal Statusmentioning
confidence: 99%